Pengaruh Faktor-Faktor Fundamental Terhadap Harga Saham Perusahaan Manufaktur Subsektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2019-2023 - Adinda Putri Rizqi; Elok Vilantika (Masyarakat Ekonomi Syariah Bogor, 2024)
This study aims to determine the effect of Return On Asset (ROA), Earning Per Share (EPS), and Debt to Equity Ratio (DER) on stock prices in food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX). This study uses an associative method with a quantitative approach using secondary data in the form of quarterly financial reports of food and beverage sub-sector companies listed on the Indonesia Stock Exchange. The population used is all food and beverage sub-sector companies listed on the IDX during the 2019-2023 period, totaling 26 companies. The sampling method used is purposive sampling. The results of the study indicate that partially the ROA variable has a significant effect on stock prices in food and beverage sub-sector companies. The EPS and DER variables do not have a significant effect on stock prices in food and beverage sub-sector companies.